Застосування прецедентного підходу до розв’язання інцидентів в прикладній ІС - Шейна, О. В.; Коптев, О. О.; Шеховцова, В. І. (ХНУРЕ, 2019)
situations at the apiary using automated classifier incidents and library precedents. The obtained evaluations on the results o f the implementation o f the proposed solution to the problem situation are used to rank the precedents in the basis o f decisions, which subsequently optimizes the library of incidents and increases the efficiency o f the use o f the developed information system o f decision-making.
Keywords: Incident; precedent; information system; decisionmaking; case-law approach